BRICS, SCO and new mechanisms of Global Governance - G. Toloraya (Международная аналитика)
The paper deals in detail with the purposes of creation and functioning of BRICS. The activities of BRICS and SCO are compared; the prospects of building new political, economic and financial architecture are examined. Dialogue of civilizations is expected to develop further under the auspices of international multilateral structures.